Student Learning Independence in Digital Era through the Rumah Belajar Application at the Junior High School Level - Ridwan, Adang; Daris; Astuti, Andri; Sawitry, Maryanti; Saputra, Erdiyan; Sariningrum, Lindang Mei Dwi (PROJECT (Professional Journal of English Education), 2026)
The Rumah Belajar application can be accessed through smartphones, allowing these devices to be used not only for phone calls, messaging, watching videos, accessing social media, or playing games, but also for learning purposes. In the teaching and learning process, teachers are expected to use learning media rather than relying only on textbooks, markers, and whiteboards. This study aims to examine the effect of using the Rumah Belajar application as a learning medium on students’ learning independence in English subjects. This study employed a quantitative research design. The participants were 46 eighth-grade students from two classes at an Islamic Integrated Junior High School in Jambi City. Data were collected through observation and questionnaires. The data were analyzed using descriptive quantitative analysis. The results show that learning activities using the application were carried out through three stages: preparation, implementation, and closing. The statistical results indicate a significant effect of the application-based learning media on students’ learning independence in English, as the calculated t-value was higher than the critical value and the significance level was below 0.05. This finding indicates that the Rumah Belajar application has a positive influence on students’ learning independence.